IoT Based Sustainable Smart Walking Assistance System Using Light Weight Nagaland Bamboo - Sileo, Vikedokho; Baskaran, Shakila; Marimuthu, Prakash (2024 International Conference on Advancement in Renewable Energy and Intelligent Systems (AREIS), 2024)
Blindness is basically the lack of vision occasionally cannot be rectified with eyeglasses or lens. Visually challenged people have difficulty in interacting with the environment. So, they have to rely on someone else to move. With the proposed sustainable light-weight bamboo smart walking stick, they will be able to travel from one place to the other in a convenient way without relying much on others, thus easing the carbon footprint in the environment. The sturdy sustainable light-weight bamboo walking stick makes use of different sensors, to sense the area and detects whether it is suitable for its user to move. The sensor integrated Arduino controller is also connected with a buzzer alarm which acts as an immediate output. Based on the detection of obstacles by the sensors, the buzzer will sound. Since the traditional stick is not eco- friendly and costly, it creates a lot of downsides in its application. On the other hand, the light-weight bamboo smart walking stick is more efficient and affordable. The power consumption of the module is low and also the durability and resilience of bamboo cannot be compared with traditional white cane.